Concurrent Lymphoma and Pancreatic Adenocarcinoma - Lai, Jiun Miin; Crowley, Peter; Nikfarjam, Mehrdad (JOP. Journal of the Pancreas, 2011)
Context Retroperitoneal lymph node enlargement in patients with pancreatic cancer is sometimes treated as incurable disease. Non-metastatic causes of lymphadenopathy should however be considered. Case reports Two cases of significant retroperitoneal lymphadenopathy in the setting of pancreatic cancer, treated by pancreaticoduodenectomy and lymph node dissection are described. Both cases had a final diagnosis of concurrent pancreatic cancer and lymphoma with no evidence of pancreatic lymph node metastasis on histopathology. Discussion We discuss the patterns of normal lymph node involvement in pancreatic cancer and lymphoma. Conclusion Interpretation of staging imaging is important in patients with pancreatic cancer. Not all enlarged lymph node should be attributed to pancreatic cancer. Image: Aorto-caval lymph node.